Bauxite Residue: A viable filler for asphalt mix - Jayvant Choudhary; Brind Kumar; Ankit Gupta (Građevinar)
Bauxite residue or red mud is used as surrogate filler for stone dust in asphalt concrete mixes. Asphalt mixes with both fillers were designed and strength, volumetric properties, and performance against various distresses (rutting, cracking, long-term aging, and moisture susceptibility) were assessed. Red mud mixes displayed higher Marshall stability and resistances against rutting and cracking due to mineralogy and fineness of red mud. Alkaline and hydrophobic nature of red mud produced satisfactory moisture resistant mix. However, red mud mixes had higher optimum binder content and lower long-term aging resistance which was attributed to porous nature of red mud.